P192 First event of acute intestinal inflammation and the risk of progression to Inflammatory bowel disease: a retrospective analysis. (21st January 2022) - Levartovsky, A; Ovdat, T; Barash, Y; Ben-Shatach, Z; Skinezes, Y; Jesin, S; Klempfner, R; Grossman, E; Kopylov, U; Ben-Horin, S; Ungar, B
Abstract: Background: Episodes of acute ileitis or colitis have been associated with future development of inflammatory bowel diseases (IBD). Nevertheless, the incidence of IBD among patients diagnosed with acute intestinal inflammation is currently unknown. We aimed to assess the risk for future development of IBD based on clinical and radiographical features of patients presenting with abdominal symptoms to the emergency department (ED) and undergoing urgent computerized tomography (CT) of the abdomen. Methods: We created an electronic data repository of all patients visiting the ED at our medical center and undergoing abdominal CT between 2011–2020. We searched the computerized database for patients diagnosed with Crohn's disease (CD) or ulcerative colitis (UC) during a visit to the gastroenterology department within maximal follow-up time of 9 years from the index-admission to the ED. Statistical analysis including multivariate models identified the risk and possible predictors of patients to develop IBD. Results: Overall, 1551 patients visited the ED and underwent abdominal imaging with abnormal findings. The radiographic parameters reported the most on abdominal CT scans were bowel wall thickening, fat infiltration, and abdominal free fluid. Twenty-three patients (1.5%) were eventually diagnosed with IBD (19 CD, 4 UC) at gastroenterological follow-up with a median of 60 days (IQR 30–120) from the time of the ED admission. Patients with a future IBD diagnosis were significantly younger (28 vs 51 years, p<0.001) and had higher rates of diarrhea as a presenting symptom (17.4% vs 2.6%, p< 0.001) compared to patients who did not develop IBD. On multivariate analysis, age (p< 0.001(and colitis on imaging (p=0.001) were associated with the development of IBD. Conclusion: IBD would be eventually diagnosed only in a minority of patients presenting with ileitis or colitis on abdominal CT. Younger age, diarrhea as a presenting symptom and colitis on imaging are predisposing factors.